LIQUIDITY RATIO ANALYSIS IN PREDICTING POTENTIAL FINANCIAL DIFFICULTIES AT THE COMPANY PT. ULTRAJAYA MILK INDUSTRY - Rico Nur Ilham; Widodo Endi Prasetia; Cut Afra Humaira; Dina Salsabila; Irada Sinta (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The paper discusses the analysis of liquidity ratios in predicting potential financial difficulties in PT Ultrajaya Milk Industri. Liquidity ratios are used to measure the company's ability to pay short-term obligations. The research method employed is empirical research with a descriptive qualitative approach. The data used is quantitative data from secondary sources, specifically the financial statements of PT Ultrajaya Milk Industry & Trading Company Tbk. The objectives and benefits of liquidity ratios include measuring the company's ability to pay obligations, comparing inventory to working capital, and serving as a planning tool for the future. Liquidity ratios are utilized to assess a company's ability to pay third-party obligations. The analysis of liquidity ratios at PT. Ultrajaya Milk Industri, Tbk indicates that the company has a strong ability to pay debts. The company's current ratio and quick ratio are both above 100%, demonstrating an excess of current assets and the ability to pay debts. Evaluation of liquidity ratios should consider industry context, comparison with competitors, and other analyses related to the company's financial policies and strategies. It is also important to consider the balance between liquidity and long-term growth.